Environmental and economic consequences analysis of cropping systems from fragmented to concentrated farmland in the North China Plain based on a joint use of life cycle assessment, emergy and economic analysis. (1st December 2019) - Yang, Xiaolei; Sui, Peng; Zhang, Xuepeng; Dai, Hongcui; Yan, Peng; Li, Chao; Wang, Xiaolong; Chen, Yuanquan
Abstract: The policy of land rental activity from fragmented to concentrated farmland has been overwhelming encouraged by the Chinese government. The land management policy has paid more attention on the investigation of its economic and social performances of land rental activity, while information on its environmental consequence is still lacking. This study, therefore, compared the environmental and economic performances of small (SF) and large scale (LF) farms based on emergy evaluation (EME), life cycle assessment (LCA) methods, and economic analysis (EA), which reflected a land rental activity from fragmented to concentrated farmland in the North China Plain (NCP). The EME results showed that the environmental loading ratio of the LF was 5.0% lower, while the emergy yield ratio and emergy sustainability index of the LF were 1.48% and 8.0% higher, respectively, than that of the SFs. The LCA results demonstrated that the area-based and yield-based environmental impact indices of the LF were 28.8% and 18.3% lower than that of the SF, respectively. These results indicate that the environmental consequences of the cropping system were improved when the farmland was managed in a concentrated model instead of a fragmented model. In addition, the EA results showed that the income to cost ratio of the LF was reduced by 47.46% compared to that of the SF, due to high land rental costs in the LF. Nevertheless, the total profit of the LF was 1719.3% higher than that of the SF due to its lager farm scale. Also, the owner's total profit of the SF was increased by 195.5% compared to the farming by themselves in their own farmland instead of renting them out. These results showed that scale management can promote both managers who rented out and into the farmland to increase their annual total incomes. In conclusion, the concentrated farmland would be a platform for the improvement of environmental consequences of cropping systems in the NCP. Highlights: Environmental and economic consequences of small and large farms are compared. The paper performed a joint use of LCA, emergy and economic analysis. Environmental consequence of concentrated farmland was better than fragmented farm. Concentrated farmland improved economic benefit of farmers.